Contemporary urban planning: the importance and consequences of citizen participation in the processes and decisions about urban space - Mussi, Andréa Quadrado (Interações, 2018)
This paper contemplates on the importance of empowering local communities to develop urban interventions. One example of such importance is observed on the revitalization of a square of Passo Fundo, RS, Brazil, conducted through a public/private partnership. A survey of user satisfaction and behavior presents the appropriation of the square. Planning, design and urban management actions performed throughout a period of eight years boosted crucial changes in the neighborhood urban dynamic.